Perlindungan Hukum Terhadap Penggugat Dalam Perkara Penyerobotan Tanah (No. Perkara 337/Pdt.G/2023/Pn.Mdn) Ditinjau Dari Hukum Perdata - Salman Lubis; Fany May Sarah Sitohang; Delva Fitria; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu (LPPM Politeknik Pratama, 2023)
Legal protection for plaintiffs in land grabbing cases needs to be carried out by law enforcers to avoid undesirable incidents. Land grabbing has a detrimental impact on parties whose ownership rights are illegally owned by perpetrators who do not want to suffer losses. The plaintiff has rented a plot of land and buildings to the defendant for Rp. 15,000,000/year, but it has been 11 years now that the defendant has not had good faith in paying rent to the plaintiff, and has claimed that the land and building rented by the defendant to the plaintiff belong to the defendant. Before the plaintiff brought this case to court, the plaintiff had first carried out an injunction through the plaintiff's attorney against the defendant, but the defendant did not heed it. Due to this unlawful action, the plaintiff suffered a loss of Rp. 165,000,000,- (one hundred and sixty five million rupiah). For the losses suffered by the plaintiff, the defendant must also be sentenced according to Article 1365 of the Civil Code, Article 1366 of the Civil Code, Article 1367 of the Civil Code, Article 385 paragraph (1) of the Criminal Code, or according to other laws and regulations.